Diagnostic Value of Integrated Serum Protein Carbonyl, 8-Hydroxy-2’-Deoxyguanosine, and PGC-1α Profiling for Myocardial Energy Metabolism Disorder in Ischemic Cardiomyopathy - Wang, Qingli; Liu, Bei (Journal of Medical Biochemistry, 2026)
Background: Patients with ischemic cardiomyopathy (ICM) often have abnormalities in myocardial energy metabolism, whereas conventional cardiac function indices may not capture metabolic injury in a timely manner. This study aimed to evaluate the diagnostic value of combined serum protein carbonyl (PC), 8-hydroxy-2’-deoxyguanosine (8-OHdG), and peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) detection for myocardial energy metabolism disorder in patients with ICM. Methods: A total of 167 patients with ICM hospitalized between June 2024 and October 2025 were retrospectively enrolled. According to myocardial energy metabolism status, they were divided into an energy metabolism disorder group (n=78) and a non-disorder group (n=89). Serum PC, 8-OHdG, and PGC-1α levels were measured. Clinical data, cardiac function indices, and serum biomarker levels were compared between the two groups. A combined diagnostic model was then constructed using logistic regression, and receiver operating characteristic (ROC) curves were used to evaluate the diagnostic performance of single indicators and combined detection. Results: Compared with the non-disorder group, the energy metabolism disorder group showed increased PC and 8-OHdG levels and decreased PGC-1α levels, with statistically significant differences (P<0.001). Multivariate logistic regression showed that PC, 8-OHdG, and PGC-1α were independently associated with myocardial energy metabolism disorder. ROC analysis showed that the areas under the curve (AUCs) of PC, 8-OHdG, and PGC-1α alone were 0.806, 0.791, and 0.772, respectively. The AUC of the combined diagnostic score increased to 0.884, with a sensitivity of 87.18% and a specificity of 79.78%, and the AUC of the combined model was higher than that of each single indicator. Conclusion: Increased serum PC and 8-OHdG levels and decreased PGC-1α levels are closely related to myocardial energy metabolism disorder in patients with ICM. Combined detection of the three indicators shows good diagnostic performance and may provide laboratory evidence for the auxiliary identification and risk stratification of myocardial energy metabolism disorder.